Evaluation of the quality of life of pregnant women from 2005 to 2015. (July 2017) - Morin, M.; Vayssiere, C.; Claris, O.; Irague, F.; Mallah, S.; Molinier, L.; Matillon, Y.
Abstract: Over the past two decades, quality of life has become an essential preoccupation in the care of patients. Many measuring instruments are available to assess physical, psychological and social quality of life. These tools allow healthcare professionals to determine the best quality of their patients. However, the quality of life for the pregnant woman seems to be little studied. This article presents the results of a bibliographic review of publications between 2005 and 2015 – referenced in PUBMED and COCHRANE – on the quality of life of pregnant women giving birth after the 22nd week of amenorrhea. The articles were selected by a reading committee. 195 publications responding to keywords were identified. 75 articles on the problem were selected. The main countries that have published on this subject are Iran (n = 11) and Brazil (n = 9). France ranks 17th with only one publication. 74% of articles deal with quality of life for pathological pregnancies (gestational or pre-existing pathologies). 23 pathologies were identified, mainly depression (20% of items). This review reveals a growing global interest in quality of life in pregnant women. However, few studies evaluate the impact of care in terms of quality of life in pregnant women, contrary to the recommendations of different health authorities. Finally, the analysis of the various articles shows that, in general, few measurements are made to evaluate the quality of life, not requiring a standardized curve of quality of life during pregnancy. There is thus a significant lack of data to establish a standardized curve for the quality of life of pregnant women, which allows a simple comparison of quality of life measures according to the different clinical management.